2005
DOI: 10.1080/09638280400014576
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity: Clinical perceptions, neurological realities and meaningful measurement

Abstract: When you can measure what you are speaking about and express it in numbers, you know something about itbut when you cannot measure it in numbers your knowledge is of a meagre and unsatisfactory kind -it may be the beginning of knowledge but you have scarcely, in your thought, advanced to the stage of science whatever the matter may be. (Lord Kelvin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
376
0
21

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 603 publications
(398 citation statements)
references
References 25 publications
1
376
0
21
Order By: Relevance
“…For that reason, different broader definitions are used increasingly. [2][3][4] In this study, a definition introduced by the SPASM consortium 5 is used. The definition describes spasticity as disordered sensorimotor control, presenting as involuntary muscle activation following an upper motor neuron lesion, thus it includes all positive features of upper motor neuron syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, different broader definitions are used increasingly. [2][3][4] In this study, a definition introduced by the SPASM consortium 5 is used. The definition describes spasticity as disordered sensorimotor control, presenting as involuntary muscle activation following an upper motor neuron lesion, thus it includes all positive features of upper motor neuron syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…1 The literature has shown that 65-78% of individuals with chronic spinal cord injury (SCI) have symptoms of spasticity. 2,3 It has the potential to negatively influence the quality of life through restricting activities of daily living, causing pain and contributing to the development of contractures.…”
Section: Introductionmentioning
confidence: 99%
“…This definition has the benefit of being precise but has been challenged 5 and does not reflect the multidimensional nature of spasticity. For the purpose of this study, we used a relatively broader definition developed by the SPASM consortium: 6 'Disordered sensory-motor control resulting from an upper motor-neuron lesion presenting intermittent or sustained involuntary activity of muscles'. The definition distinguishes spasticity from the passive viscoelastic changes of muscle properties such as contractures, which are also associated with SCI.…”
Section: Introductionmentioning
confidence: 99%